Assessment Of Teacher Performance In Relationship With The Quality Of Educational Services In Madrasah Tsanawiyah City Of Bandung - Hidayat, Wahyu; Badrudin, Badrudin; Izzaturrahmah, Qonita (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to find out: (1) The reality of teacher performance assessment at State MTs in Bandung City. (2) The Reality of the Quality of Education Services at Bandung City Public MTs, and (3) The Relationship between Teacher Performance Assessment and the Quality of Education Services at Bandung City State MTs. This research is quantitative research using correlational methods. The data in this study were obtained by distributing a questionnaire with a Likert scale model consisting of four selected answers to 85 respondents. Data analysis techniques in this study were instrument tests (validity and reliability), statistical analysis tests, hypothesis testing (Spearman's rank correlation test), and coefficient of determination tests. The results of the study show that: (1) Teacher performance evaluation at Madrasah Tsanawiyah Bandung City is included in the moderate category, which is equal to 3.58 from the results of data processing of 85 respondents; (2)The quality of education services at Madrasah Tsanawiyah Negeri Kota Bandung, is included in the medium category, which is equal to 3.15 from the results of data processing of 85 respondents; (3) Based on the results of calculating the correlation between variable X and variable Y, a correlation coefficient of 0.573 is obtained, including the coefficient category of 0.51-0.75 meaning that there is a relationship that is quite large or strong enough. So it can be concluded that there is a relationship between teacher performance assessment and the quality of education services at Madrasah Tsanawiyah Negeri Bandung City. The results of the correlation test calculation show that the significance of teacher performance assessment with the quality of educational services is 0.000 0.05. The results of the correlation test calculation are positive, which means that if the results of the performance assessment carried out on the teacher are good, the service provided by the teacher is also good. Then, from the results of the coefficient of determination test, it was obtained (R square) of 0.328, which means that teacher performance assessment of the quality of educational services has a contribution of 32.8%.